Macroscopic study of Lesions Affecting Genital Tract of Iraqi Ewes - J., Khammas D.; S., Ibrahim N.; E., ; Buni F.; F., Alwan A. (The Iraqi Journal of Veterinary Medicine, 2013)
A total of 660 genital tract of adult ewes slaughtered at Baghdad Abattoirs, were examined for the gross pathological conditions .One hundred thirty three (20.22%) of them showed different type of abnormalities of the total genital examined, 157 (23.87%) were pregnant and the rest 503 were non-pregnant ones. Eighteen (11.46%) of the pregnant and 115 (22.86%) of the no pregnant genitalia showed pathological conditions, Ovarobursal adhesions 51(7.72%) and paraovarian cysts 35(5.31%)were the most common abnormalities recorded. In conclusion: Such kind of abnormalities observe in genitalia slaughtered ewe could be considered as the causes of temporary infertility or permanent sterility, never the less, the percentage of slaughtered pregnant ewes was too high